2023
DOI: 10.3390/ijerph20064777
|View full text |Cite
|
Sign up to set email alerts
|

Digital Addiction Intervention for Children and Adolescents: A Scoping Review

Abstract: Digital devices play a significant role in the learning and living of children and adolescents, whose overuse or addiction has become a global concern. This scoping review seeks to synthesize existing studies to investigate relevant interventions and their effects on digital addiction in children (ages 0–18). To understand the latest advances, we have identified 17 studies published in international peer-reviewed journals between 2018–2022. The findings revealed that, first, most interventions for digital addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…E-health can be applied in various stages of human development. Digital based intervention is a promising alterative intervention for adolescents with digital addiction (Ding & Li, 2023). Not only in adolescents, e health interventions can also be applied to children starting at the age of 11 years (Akgül-Gündogdu & Selçuk-Tosun, 2023) and adults aged 18 years and over (Keller et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-health can be applied in various stages of human development. Digital based intervention is a promising alterative intervention for adolescents with digital addiction (Ding & Li, 2023). Not only in adolescents, e health interventions can also be applied to children starting at the age of 11 years (Akgül-Gündogdu & Selçuk-Tosun, 2023) and adults aged 18 years and over (Keller et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Digital addiction occurs in various age groups. Child and adolescent tend to became addicted to electronical devices, online game and social media (Ding & Li, 2023), (Putra et al, 2023), (Macur & Pontes, 2021), (Baciu, 2020). 19-24 years old was population with a great number problem gamers (André et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Participating in offline activities represents an additional strategy for mitigating the risk of developing online addiction (59,60). Engaging in extracurricular pursuits, such as volunteering, arts and crafts, or athletics, can assist individuals in shifting their attention from the digital realm and fostering fresh passions and interests.…”
Section: Techniques For Preventing Online Addictionmentioning
confidence: 99%
“…Many factors contribute to overweight and obesity such as diet, genetics and environment ( 6 ). However, with the advancement of technology, people are becoming more connected to digital devices, their lifestyles are gradually moving from offline to online and they spend a lot of time in the digital world every day ( 7 , 8 ). Many studies have shown that over-reliance on digital (e.g., use of mobile phones, tablets, and computers) has become a new way of becoming overweight and obese ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%